ANALYSIS OF FISH BORN DIAGRAM TO IMPROVE THE QUALITY OF TEMPE PRODUCTS IN BONDOWOSO DISTRICT - sulfiana, Icha; Hafidzi, Achmad Hasan; Fatimah, Feti (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This research fills the knowledge gap regarding the use of Fishbone Diagrams to analyze the quality of tempe products in Bondowoso Regency, which has not been widely applied before. Most previous research tends to separate production factors, such as production processes or production machines, but this research combines all these factors in one analytical framework. The type of research used is quantitative with the object of 100 tempeh industries in Bondowoso, using questionnaires and observations for primary data collection. The novelty of the research lies in the application of the Fishbone Diagram in the context of the Bondowoso tempe industry. The practical implication is to provide recommendations for tempe industry players to improve product quality through improving production processes, using appropriate machines, selecting quality raw materials, as well as improving workforce skills and relationships with suppliers. These steps are expected to improve the quality of tempeh, expand the market, and strengthen the position of the local tempeh industry.